2015
DOI: 10.1086/681263
|View full text |Cite
|
Sign up to set email alerts
|

The Acid Test: pH Tolerance of the Eggs and Larvae of the Invasive Cane Toad (Rhinella marina) in Southeastern Australia

Abstract: Invasive cane toads are colonizing southeastern Australia via a narrow coastal strip sandwiched between unsuitable areas (Pacific Ocean to the east, mountains to the west). Many of the available spawning sites exhibit abiotic conditions (e.g., temperature, salinity, and pH) more extreme than those encountered elsewhere in the toad's native or already invaded range. Will that challenge impede toad expansion? To answer that question, we measured pH in 35 ponds in northeastern New South Wales and 8 ponds in the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 68 publications
1
6
1
1
Order By: Relevance
“…However, our studies falsify this prediction. In other work, we have shown that neither pH nor salinity levels in this area are likely to prevent successful reproduction by cane toads (Wijethunga, Greenlees, & Shine, , ). A third possibility, addressed in the current study, is that lower temperatures will constrain toad reproduction in more southerly regions.…”
Section: Discussionmentioning
confidence: 68%
“…However, our studies falsify this prediction. In other work, we have shown that neither pH nor salinity levels in this area are likely to prevent successful reproduction by cane toads (Wijethunga, Greenlees, & Shine, , ). A third possibility, addressed in the current study, is that lower temperatures will constrain toad reproduction in more southerly regions.…”
Section: Discussionmentioning
confidence: 68%
“…Except where stated, the following experiments were conducted in evenly lit arenas filled with aged water at a depth of 30 mm and a temperature of 25°C, which is within the thermal range measured in natural ponds in the Northern Rivers region (Wijethunga et al., ). This relatively shallow water depth was deemed appropriate as R. marina tadpoles often occur in shallow water (Crossland & Shine, ), and is also consistent with the protocols of similar experiments (Leu et al., ; Sontag et al., ; Waldman & Adler, ; Wassersug & Hessler, ).…”
Section: Methodsmentioning
confidence: 90%
“…Except where stated, the following experiments were conducted in evenly lit arenas filled with aged water at a depth of 30 mm and a temperature of 25°C, which is within the thermal range measured in natural ponds in the Northern Rivers region (Wijethunga et al, 2015).…”
Section: Specific Experimentsmentioning
confidence: 96%
See 1 more Smart Citation
“…Estos factores pueden ser identificados como primarios (Factores bióticos o ambientales) o secundarios. Estos últimos operan a través de la ecología reproductiva y el comportamiento de los adultos, mediante la selección de sitios de puesta, lo que afecta directamente el ambiente de las larva, tal como se muestra en la Figura 2.2 (Alford & Richards, 1999) En lo que respecta a las tasas de crecimiento los factores que más influyen son, la competencia, la cual puede ser tanto intra como interespecífica y los factores ambientales, que describen la calidad del agua como ser oxígeno disuelto, pH, así como también factores físicos como la temperatura y el fotoperiodo (Loman, 2016;Wijethunga, Greenlees, & Shine, 2015;Woolrich-Piña, Smith, & Lemos-Espinal, 2015).…”
Section: Descripción Del Desarrollo Normalunclassified